2012
DOI: 10.1371/journal.pone.0036210
|View full text |Cite
|
Sign up to set email alerts
|

Hypocotyl Transcriptome Reveals Auxin Regulation of Growth-Promoting Genes through GA-Dependent and -Independent Pathways

Abstract: Many processes critical to plant growth and development are regulated by the hormone auxin. Auxin responses are initiated through activation of a transcriptional response mediated by the TIR1/AFB family of F-box protein auxin receptors as well as the AUX/IAA and ARF families of transcriptional regulators. However, there is little information on how auxin regulates a specific cellular response. To begin to address this question, we have focused on auxin regulation of cell expansion in the Arabidopsis hypocotyl.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
133
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(143 citation statements)
references
References 106 publications
(192 reference statements)
10
133
0
Order By: Relevance
“…This suggests that following shade treatment, it might be possible to observe a temporal delay in the regulation of auxin-responsive genes between cotyledons and hypocotyls. To verify this prediction, we analyzed shade regulation of genes that rapidly (within 30 minutes) respond to picloram (a synthetic auxin) application in hypocotyls (Chapman et al, 2012). We detected expression of 46 (70%) picloram-regulated genes in our data set, among which 43 were regulated by shade.…”
Section: Shade-regulated Expression Of a Subset Of Auxinresponsive Gementioning
confidence: 92%
See 2 more Smart Citations
“…This suggests that following shade treatment, it might be possible to observe a temporal delay in the regulation of auxin-responsive genes between cotyledons and hypocotyls. To verify this prediction, we analyzed shade regulation of genes that rapidly (within 30 minutes) respond to picloram (a synthetic auxin) application in hypocotyls (Chapman et al, 2012). We detected expression of 46 (70%) picloram-regulated genes in our data set, among which 43 were regulated by shade.…”
Section: Shade-regulated Expression Of a Subset Of Auxinresponsive Gementioning
confidence: 92%
“…However, while in the hypocotyl, the expression levels of many of these genes continued to rise until 90 min; in the cotyledons, the peak of expression was typically at 45 min ( Figure 4A). As this initial analysis did not provide evidence for an obvious temporal delay of auxin-regulated genes between hypocotyls and cotyledons, we tested this further by analyzing the expression of genes in response to a 2-h picloram application (Chapman et al, 2012). These genes displayed a more organ-specific shade response but did not provide evidence for an earlier auxin response in cotyledons than hypocotyls (Supplemental Figure 4A).…”
Section: Shade-regulated Expression Of a Subset Of Auxinresponsive Gementioning
confidence: 99%
See 1 more Smart Citation
“…In response to shade and high temperatures, and possibly under diurnal conditions or in response to Suc (Lilley et al, 2012), PIFs induce auxin synthesis and responses (see below), placing PIFs upstream of auxin signaling. However, transcriptome analysis to identify auxin-regulated genes expressed in elongating hypocotyls (Chapman et al, 2012) suggested a model whereby auxin might promote growth partly through PIF-dependent pathways, potentially placing auxin upstream of PIFs, although this possibility needs further testing. Importantly, pif4 pif5 double mutants displayed altered responsiveness to exogenous auxin, suggesting that PIFs modulate auxin signaling (Nozue et al, 2011;Hornitschek et al, 2012).…”
Section: Pifs As Systems Integrators Interface With Hormonal Pathwaysmentioning
confidence: 99%
“…PRE1 was initially identified as a positive regulator of GA responses , but other studies have elucidated roles of PRE1 and its homologs in growth regulation by a wide range of signals, including BR, auxin, and light (Zhang et al, 2009;Bai et al, 2012;Oh et al, 2012;Chapman et al, 2012). Overexpression of PRE1 and its rice (Oryza sativa) homolog INCREASED LAMINA INCLINATION1 (ILI1) increased BR-induced cell elongation in both Arabidopsis and rice (Zhang et al, 2009), and overexpression of PRE3/ATBS1/TMO7 suppressed the bri1 mutant ).…”
Section: Introductionmentioning
confidence: 99%